Plasma cell granuloma in oral cavity: A case report. - Edgar Reyes; Karla Zaldivar; Salvador Padilla (Universidad de Concepción., 2015)
Plasma cell granuloma is a rare benign tumor lesion that is classified and described under the pseudoinflammatory tumor category. Its occurrence in the oral cavity is rare, making diagnosis and treatment really difficult, as it bears some clinical similarity with malignant tumor diseases. Proper diagnosis and treatment of PCG requires performing biopsy and a histopathological/immunohistochemical study to rule out possible plasma and neoplastic cell dyscrasias. Consequently, the use of these auxiliary diagnostic devices will enable us to provide the appropriate treatment for the patient. In this study, we present the case of a 63-year-old female patient with a tumor/ulcerative lesion of the left buccal mucosa of a month of evolution and a tumor/ulcerative lesion on the right buccal mucosa of 15 days of evolution after the onset of the first lesion. The patient was treated successfully for a period of one year with immunosuppressive drugs, and to date the disease is inactive. The purpose of this paper is to show one of the most unusual locations in the oral cavity affected by this pathological entity, its clinical and histological features, and establish the differential diagnosis correctly with other malignant or benign disease entities, suggesting the most suitable treatment for this type of condition.